2018
DOI: 10.1097/rlu.0000000000002171
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Multiple Primary Intestinal-Type Adenocarcinoma in the Lung by 18F-FDG PET/CT

Abstract: A 74-year-old man with multiple soft tissue lesions in the lung, which were suspected to be metastatic neoplasms, underwent F-FDG PET/CT scan to detect primary malignancy. The images demonstrated that the lung and 2 retroperitoneal lymph nodes were the only affected organ or tissues with suspected primary lung neoplasms. Multiple intestinal-type adenocarcinoma was eventually diagnosed by CT-guided transthoracic needle aspiration biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…3 As an advanced screening method, PET/ CT can offer both precise anatomical positioning and functional metabolism imaging, which plays an essential role in the diagnosis and treatment of tumours in recent years. [4][5][6] Maximum standard uptake value (SUVmax) is a common used semi-quantity parameter in PET/CT inspection. It can measure the activity level of tissue metabolism that is strongly correlated with the speed of cell division and proliferation.…”
mentioning
confidence: 99%
“…3 As an advanced screening method, PET/ CT can offer both precise anatomical positioning and functional metabolism imaging, which plays an essential role in the diagnosis and treatment of tumours in recent years. [4][5][6] Maximum standard uptake value (SUVmax) is a common used semi-quantity parameter in PET/CT inspection. It can measure the activity level of tissue metabolism that is strongly correlated with the speed of cell division and proliferation.…”
mentioning
confidence: 99%
“…The typical signs of pulmonary enteric adenocarcinoma on CT are solid nodules or masses, similar to other primary lung cancers, whereas a pulmonary enteric adenocarcinoma manifested as widespread intrapulmonary opacities in both lungs is difficult to be distinguished from pneumonia 8 . Hu et al 9 reported a case with multiple hypermetabolic soft tissue lesions in the lung, whose diagnosis was confirmed as intestinal-type adenocarcinoma, whereas our case manifested as diffuse intense FDG uptake in both lungs. Widespread abnormal FDG activity in both lungs can be seen due to many different etiologies 10–15 .…”
mentioning
confidence: 54%